Zinc and epilepsy: Is there a causal relation between them? (2006)
Introduction. Zinc is a fundamental trace element for an adequate nervous system function. It has been suggested that in the brain, a zinc homeostasis alteration may be associated with the genesis of epilepsy, although it is not yet determined if concentrations of zinc are a cause or a consequence of seizures. Another poorly studied aspect is the relationship between antiepileptic drugs and the neuronal zinc behaviour. Development. We perform a systematic review of the literature to evaluate the role that zinc plays in epilepsy as well as the antiepileptic effect of zinc concentrations. Databases such as MEDLINE, EMBASE, SCISEARCH and LILACS were consulted from January 1974 to July 2005. All articles published in English and Spanish were considered. A manual review of the references present in each article was done in order to identify the articles that the electronic search may have not found itself. The title and abstract of the potential articles were analyzed before asking for the complete article. However, articles that seemed ambiguous were completely analyzed later to establish their relevance. Conclusions. Clinical research in epilepsy presented contradictory results. In fact, the reviewed studies, both animal and human, did not give enough evidence to determine if organic zinc variations are directly related to epilepsy. Most of them gave not statistically significant results. © 2006, Revista de Neurología.